2007
DOI: 10.1007/s00405-007-0496-5
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the oral cavity in young patients: a matched-pair analysis

Abstract: There is an increased incidence of oral squamous cell carcinoma (SCC) in young patients. However, the literature concerning prognosis for young patients with oral SCC is conflicting. The aim of this study was to compare the survival rates of patients under 45 years of age and diagnosed with SCC of the oral cavity with those of patients older than 45 years. A retrospective review of 28 patients under 45 years of age with SCC of the oral cavity was performed. We matched each of these patients by sex, tumor site,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
1
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 25 publications
6
28
1
7
Order By: Relevance
“…None of our cases had a special risk factor or habit. It was consistent with some previous studies, whereby no major risk factor (smoking and/or drinking) were prepresent (3,8). Low alcohol consumption due to Islamic rules, and risky behaviors among people of this province such as chewing tobacco and eating spicy foods might explain showing no risk factor in our cases.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…None of our cases had a special risk factor or habit. It was consistent with some previous studies, whereby no major risk factor (smoking and/or drinking) were prepresent (3,8). Low alcohol consumption due to Islamic rules, and risky behaviors among people of this province such as chewing tobacco and eating spicy foods might explain showing no risk factor in our cases.…”
Section: Discussionsupporting
confidence: 93%
“…Sasaki et al believed that there are minimal differences between the younger and the older patients in clinical and histological characteristics (2). But other studies have reported fewer recurrences and distant metastasis and better survival rate in the young patient population (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, some studies showed the more biological behavior and clinical course of OSCC in young patients [2,9,10]. But in other studies observed no difference between clinical course and prognosis of OSCC in two groups of age [4,11,12]. Even, Udeabor and et al showed that young patients have a better prognosis than old patients [8].…”
Section: Introductionmentioning
confidence: 98%